Preoperative risk evaluation in patients over 75 years candidates to non-cardiac and cardiac surgery - Alessandro Boccanelli; Pompilio Faggiano (Monaldi Archives for Chest Disease, 2017)
In the 24th and 25thof June 2016, 80 national experts were invited to Rome from The Italian Society of Geriatric Cardiology and the Italian Association of Cardiovascular Prevention and Rehabilitation to revise the current knowledge on the perioperative risk in the elderly. Cardiologists, geriatricians, heart and general surgeons and anesthesiologists discussed the topic with the objective of reaching a consensus and to launch observational research and registries in the field of perioperative risk evaluation in the elderly. The introduction of objective measures of frailty on top of traditional cardiac evaluation in the different surgical contexts could allow for a more precise definition of “surgical risk”, appropriate perioperative management and postoperative outcome.